DNA I-motif : application to epigenetics and biosensing. - Xu, Baochang (2014)
DNA i-motif is an intercalated quadruplex structure formed by association of hemi- protonated C•CH+ pairs. The fact that i-motif folding sequences are widely present in oncogenic regions and human telomeric DNA suggests that the formation of i-motif may be associated with the regulation of oncogene expression. Due to the paramount significance of those regions to the gene transcription and cell apoptosis, i-motif has become an attractive drug target for cancer chemotherapy and gene transcription modulation. On the other hand, the i-motif sequences can be reversibly and rapidly oscillated from a stable quadruplex structure to a random coil by adjusting the pH. This renders i-motif a great potential as nanomolecular devices in the development of biosensors. Although the aforesaid significances in biology and nanotechnology have been investigated, some challenges still remain to be drilled. For example, due to the fast dissociation and association process, the mechanism of i-motif folding and unfolding between two different states is still unclear. Besides, the effects of i-motif structural changes and folding properties induced by various chemical modifications remain ambiguous. Furthermore, although a lot of i-motif based nanomachines, logic gates, nanoclusters have been developed, applications of i-motif to biosensing and bioimaging haven’t been well explored.